2012
DOI: 10.1021/cs300296x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synthesis of Silanols from Hydrosilanes and Applications

Abstract: In recent years reusable and highly active metal-nanoparticle catalysts were developed for the selective transformation of hydrosilanes into the corresponding silanols using water as the oxidant. The catalysts are much more active than conventional homogeneous ones under ambient conditions. In this perspective, we summarize known catalyst systems as well as stoichiometric methods for the synthesis of silanols from hydrosilanes. Plausible pathways for the hydrolytic oxidation of hydrosilanes on metal nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 111 publications
(230 reference statements)
1
84
0
1
Order By: Relevance
“…53 Interestingly, although the synthesis of silanols from hydrosilanes have been reported using water as an oxidant, 54 the development of environmentally benign, highly selective, and practical processes for synthesizing silanols is still highly desirable. 55 In this context, Kaneda and coworkers reported a highly efficient method for the green synthesis of silanols from hydrosilanes in 2008. 56 They found that the silver nanoparticles supported on hydroxyapatite (Ag-HAp) exhibited high catalytic activities for the selective oxidation of hydrosilanes using water as a green oxidant without the use of organic solvents (Scheme 13).…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…53 Interestingly, although the synthesis of silanols from hydrosilanes have been reported using water as an oxidant, 54 the development of environmentally benign, highly selective, and practical processes for synthesizing silanols is still highly desirable. 55 In this context, Kaneda and coworkers reported a highly efficient method for the green synthesis of silanols from hydrosilanes in 2008. 56 They found that the silver nanoparticles supported on hydroxyapatite (Ag-HAp) exhibited high catalytic activities for the selective oxidation of hydrosilanes using water as a green oxidant without the use of organic solvents (Scheme 13).…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…Interest in organosilane chemistry has increased rapidly in recent years, 1 including the development of silicon-based materials 2 and many biomedically relevant agents. 1a,3 The recent expanding use of these compounds has included their participation in a wide variety of chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…1a,3 The recent expanding use of these compounds has included their participation in a wide variety of chemical transformations. Such synthetic activities include silicon-based cross-coupling reactions, 4 oxidations, 5 silanol hydrogen bond donor catalysts, 6 and as directing groups for C–H functionalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide utility of silanols and silyl ethers requires efficient synthetic procedures from available precursors. Nowadays, the synthesis of silanols may be performed from chlorosilanes, siloxanes, or hydrosilanes via hydrolysis, nucleophilic substitution, and oxidation, respectively. The catalytic methods for Si‐H oxidation occurring in the presence of transition metals have gained much attention .…”
Section: Introductionmentioning
confidence: 99%